FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN ALAT KONTRASEPSI PASCA SALIN DI RUANG NIFAS RSUD PANGERAN JAYA SUMITRA - Norhalimatussa'diah Norhalimatussa'diah; Ika Friscila; Fadhiyah Noor Anisa (Health Sciences Journal, 2023)
Family planning programs prevent maternal and child mortality because they help married couples avoid high-risk pregnancies, reduce the risk of maternal death through pregnancy prevention, delay, gestational age and reduce pregnancy. The high population growth rate is due to the low coverage of post-saline family planning use which is influenced by several factors. Childbirth as many as 75.4%, of which 8.7% of mothers do not use postpartum contraceptive methods. The purpose of the study was to analyze the factors that influence the selection of postpartum contraceptives in the postpartum room of Pangeran Jaya Sumitra Hospital, Kotabaru Regency.The research method uses a cross-sectional approach analytical survey method. This research will be carried out in the postpartum room of Pangeran Jaya Sumitra Hospital, Kotabaru Regency in January 2023. The population is all postpartum mothers recorded from November 2022 to January 2023 as many as 159 people. Samples using accidental sampling techniques as many as 30. Data collection using questionnaires analyzed using frequency distribution and Chi Square test with a signification level of 5% (α=0.05).The results showed that most respondents were well informed as many as 18 people (53.3%), had the support of their husbands as many as 19 people (63.3%), did not use postpartum contraceptives as many as 11 people (36.7%). There is an influence of knowledge on the selection of post-saline contraceptives (pvalue = 0.0060.05). There was an effect of husband support on the choice of post-saline contraceptives (pvalue = 0.00280.05). So that in this study the knowledge and support of the husband influenced the selection of post-saline contraceptives.